Retorika Visual Kampanye Kesehatan Mental Di Instagram: Antara Estetika Dan Ramah - RIhi, Samuel (JURNAL Dasarrupa: Desain dan Seni Rupa, 2025)
The growing number of visual campaigns on mental health issues on Instagram showcases diverse content that is aesthetically engaging but not always psychologically inclusive, especially for individuals with lived experiences of mental health challenges. A key issue arises when visual messages fail to build emotional connection or convey meaning relevant to their intended audience. This study aims to examine how visual elements in mental health campaigns are constructed, organized, and interpreted by such audiences. Using a qualitative descriptive approach, the analysis draws on Sonja K. Foss’s visual rhetoric theory, integrated with visual layout principles—emphasis, sequence, balance, and unity—and narrative elements such as coherence and fidelity. The findings suggest that visual beauty does not ensure effective communication if it lacks symbolic relevance, emotional sensitivity, and experiential resonance. Educational content with clear structure, empathetic tone, and integrated visual components tends to be better understood, though challenges in text readability and visual accessibility remain. Mental health campaigns should not only be visually appealing but also inclusive, non-stigmatizing, and emotionally considerate. Ensuring coherence between visuals, captions, and hashtags is essential to deliver a unified message that truly connects with the intended audience and reflects the complexity of their lived experiences.